Psicanálise e literatura : o corpo humilhado em Lima Barreto - Pimenta, Shyrley (2007)
This study investigates and elaborates considerations on the humiliated body in the life and work of Brazilian writer Lima Barreto. To accomplish this, a dialog is undertaken between Psychoanalysis and Literature, resorting to, among others, the theories formulated by Birman, Freud and Lacan. The privileged forms of subjectivization in modern times, such as narcissism, masochism and voluntary servitude, are discussed as means of protection against abandonment, which is triggered in the subject by the humiliation inflicted to the father figure in the Western world, as well as the emergence of modernism, that challenges the concepts of self and consciousness, emphasizing the unconscious and the Psychoanalysis as important ideas in modern days. This research also deals with, in the same context of modernity, the process of subjectivization of Lima Barreto, the mechanisms of defense adopted by him to confront the abandonment and the humiliations he suffered, specially the ones due to his skin color and social class. Through biographical reconstruction and reading, analysis and interpretation of this writer s works, an effort was made to identify the means he used to confront the reality, notably the function of literary writing. It is possible to conclude that the attempts of Lima Barreto to rebuild his singularity and battle the traumas of his own existence through the process of literary creation turned out fruitless, in face of the voluntary submission to servitude: to the period s culture, to the bureaucratic work, to the Government and to the deadly enjoyment provided by binge drinking. The writer was not able to organize and find meaning to the chaos of his existence, being swallowed by the void and the impetus of death that followed him since his childhood. This didn t allow him to properly process losses, mourning, abandonment, the tragic legacy of his own personal history and the social and historical context in which he lived.